ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI JAGUNG SERTA EFISIENSI TEKNIS DI KABUPATEN KUPANG - Jullyo Gideon Rohi; Ratna Winandi; Anna Fariyanti (Forum Agribisnis, 2018)
Corn (Zea mays L.) is a potential agribusiness commodity in meeting food needs. In the national economy, corn is the second largest contributor after rice in the food subsector. One potential area for corn production is Kupang Regency which has a lot of marginal lands (dry land). This study aims to determine the factors that influence the production and technical efficiency of corn farming in Kupang Regency. This study, using the Cobb-Douglas production function method, is a functional form of the corn production function in the study area and the Stochastic Frontier method is estimated using the Ordinary Least Square (OLS) and Maximum Likelihood Estimation (MLE) methods. The results showed that all the variables in the significant model were soil, seeds, Urea, KCL, SP36, pesticides and had signs that matched expectations. The study also found that farmers were technically efficient with an average of 75 percent and factors that had a significant influence on increasing technical personnel, namely age, formal education and income.